CLASSIFICATION OF Pc 1 AND Pi 1 WAVES OBSERVED IN HIGH LATITUDES - ナガタ, タケシ; ヒラサワ, タケオ; フクニシ, ヒロシ; アユカワ, マサル; サトウ, ナツオ; フジイ, リョウイチ; カワムラ, マコト; NAGATA, Takesi; HIRASAWA, Takeo; FUKUNISHI, Hiroshi; AYUKAWA, Masaru; SATO, Natsuo; et al. (1980)
P(論文) A classification of the ULF-waves in the pc 1 and pi 1 frequency range was attempted on the basis of recent data (1976-78). Referring to the spectral structures of ULF waves, their similarities at the conjugate pair stations, their association with SC and SI events, and the correlations between auroras and VLF, it is shown that pc 1 and pi 1 ULF waves can be classified into six types with nine subclasses, as summarized in Table 1. departmental bulletin paper